Effects of Healthy Ageing on Precision and Binding of Object Location in Visual Short Term Memory - Pertzov, Yoni (Psychol Aging, 2014)
Visual short term memory (STM) declines as people get older, but the nature of this deterioration is not well understood. We tested 139 healthy subjects (19–83 years) who were first required to identify a previously seen object and then report its location using a touchscreen. Results demonstrated an age-related decline in both object identification and localization. Deterioration in localization performance was apparent even when only 1 item had to be remembered, worsening disproportionately with increasing memory load. Thus, age-dependent memory degradation cannot be explained simply by a decrease in the number of items that can be held in visual STM but rather by the precision with which they are recalled. More important, there was no evidence for a significant decrease in object-location binding with increasing age. Thus, although precision for object identity and location declines with age, the ability to associate object identity to its location seems to remain unimpaired. As it has been reported that binding deficits in STM might be the first cognitive signs of early Alzheimer’s disease (AD), the finding that object-location binding processes are relatively intact with normal aging supports the possible suitability of using misbinding as an index measures for probing early diagnosis of AD.